The cycle relationship between environmental, social & governance (ESG) disclosure and company financial performance - Chin, Chee Kean; Lai, Hena Pei Loo; Neo, Si Ling (2017)
In recent decades, non-financial information such as ESG disclosure has become a trend for investors in making investment decision. Hence, many researches regarding ESG disclosures have been conducted in order to justify the effect of the ESG disclosures, especially in western context. The main purpose of this study is to examine the existence of cycle relationship between ESG disclosure and corporate financial performance among the countries selected in FTSE4Good ASEAN 5 Index, which are Malaysia, Thailand and Singapore. The secondary data was extracted from Bloomberg database for period 2011 to 2016. Besides, top 100 companies based on market capitalization in each respective country is used as study sample. The ESG disclosure of corporate is represented by ESG disclosure score, while ROE, ROA, EPS, Tobin’s Q, and Price to book ratio are used to measure the corporate financial performance. All of these data are collected from Bloomberg. This study is known as cross sectional study, whereby analyses are conducted in period basis and two years lag effect was assumed in this study, to test how corporate financial performance in period 1 (2011-2012) influences ESG disclosure score in period 2 (2012-2014), and how period 2 ESG disclosure score affects corporate financial performance in period 3 (2015-2016). The empirical results of this study found positive cycle relationship exists in Malaysia, no cycle relationship in Thailand, and a negative cycle relationship in Singapore.